Taltirelin is a superagonist at the human thyrotropin-releasing hormone receptor - Thirunarayanan, Nanthakumar; Raaka, Bruce M.; Gershengorn, Marvin C. (Frontiers in Endocrinology, 2012)
Taltirelin (TAL) is a thyrotropin-releasing hormone (TRH) analog that is approved for use in humans in Japan. In this study, we characterized TAL binding to and signaling by the human TRH receptor (TRH-R) in a model cell system. We found that TAL exhibited lower binding affinities than TRH and lower signaling potency via the inositol-1,4,5-trisphosphate/calcium pathway than TRH. However, TAL exhibited higher intrinsic efficacy than TRH in stimulating inositol-1,4,5-trisphosphate second messenger generation. This is the first study that elucidates the pharmacology of TAL at TRH-R and shows that TAL is a superagonist at TRH-R. We suggest the superagonism exhibited by TAL may in part explain its higher activity in mediating CNS effects in humans compared to TRH.